2009
DOI: 10.1139/x09-072
|View full text |Cite
|
Sign up to set email alerts
|

Response of ectomycorrhizal community structure to gap opening in natural and managed temperate beech-dominated forests

Abstract: Data on the impact of forest management practices on ectomycorrhizal community structure remains fragmentary and mainly originates from studies in northern coniferous forests. This study focuses on a comparison of ectomycorrhizal communities between canopy gaps and closed canopy areas within natural and managed beech-dominated forests at four locations in Europe. We used high resolution rDNA techniques to identify ectomycorrhiza-forming fungi and attempted to extract potential stand-, gap-, soil-, and selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…Ectomycorrhizal species are associated with tree roots and are highly host-specific (Grebenc et al, 2009). Thus, the response measured in this study was not surprising; lower abundance of ectomycorrhiza has been reported in similar studies from other areas (de Bellis, 2000;Grebenc et al, 2009).…”
Section: Effect Of Gaps On Biodiversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Ectomycorrhizal species are associated with tree roots and are highly host-specific (Grebenc et al, 2009). Thus, the response measured in this study was not surprising; lower abundance of ectomycorrhiza has been reported in similar studies from other areas (de Bellis, 2000;Grebenc et al, 2009).…”
Section: Effect Of Gaps On Biodiversitymentioning
confidence: 99%
“…Ectomycorrhizal species are associated with tree roots and are highly host-specific (Grebenc et al, 2009). Thus, the response measured in this study was not surprising; lower abundance of ectomycorrhiza has been reported in similar studies from other areas (de Bellis, 2000;Grebenc et al, 2009). The decrease in the number of species is directly due to harvesting; however, other indirect drivers include changes in environmental factors such as drought and temperature, which are known to affect ectomycorrhiza (Grebenc et al, 2009) as well as the fine roots of their hosts (Železnik et al, 2015).…”
Section: Effect Of Gaps On Biodiversitymentioning
confidence: 99%
“…In a fine-scale investigation, genetic structure analyses among individual fruiting bodies from a certain species at a specific location can help us better understand its distribution pattern, reproductive biology, and even ecological strategy (Dahlberg and Stenlid 1994; Bergemann and Miller 2002; Grebenc et al 2009). Here, individually mapped fruiting bodies from the field are the typical units of analyses.…”
Section: Fine-scale Genetic Analyses Of Field Samplesmentioning
confidence: 99%
“…The spatial scale at which these factors operate may differ strongly and range from an area encompassing the entire stand to close proximity of single trees. In fact, research shows that in mixed forests, microsites occupied by different species may differ from the neighbouring background in many properties important for establishing regeneration, including light conditions (Stadt and Lieffers 2000), topsoil moisture and pH (Paluch and Gruba 2012), ectohumus layer thickness (Bens et al 2006;Buck and St Clair 2014), forest floor vegetation (Saetre 1999), abundance of soil fungi (Frankland 1998) and fungal pathogens (Kotanen 2007) and mycorrhiza colonization rates (Cline et al 2007) or seedling mycorrhiza diversity (Grebenc et al 2009). …”
Section: Introductionmentioning
confidence: 99%